Preliminary exploration of cell-based SAW detection for water toxicity - Kun-Lin, Lee; Nordin, Anis Nurashikin; Voiculescu, Ioana R. (The American Society of Mechanical Engineers (ASME), 2018)
Nowadays, many surface sensing mechanisms exist, not all of them can be applied in water-based environment. Most of surface sensing techniques were developed in air-based environment. In order to obtain a potential cell-based biosensor, the sensing method needs to be reliable and repeatable in liquid environment. Therefore, we adapt existing air-based surface acoustic sensor and promote the technology into water-based applications. The goal of this study is to apply surface acoustic waves (SAW) for water-based environment sensing. We will use shear horizontal wave (SH wave) as surface sensing mechanism. SH wave is a type of surface acoustic waves (SAW) which can be used for weight/mass sensing in the air environment. Interdigitated transducers (IDTs) induce the deformation of an ST-cut quartz crystal substrate in AC source and generate waves. With a thin layer of polymer like Parylene and polyimide, the SH wave will be confined between the interface of substrate and polymer layer without suffering the energy loss due to the liquid damping from above. The fundamental frequency of the SAW device is defined by the spacing between the electrodes of IDT. The frequency of interests for this research is below 100 MHz in water-based environment. Due to the stable frequency characteristics of ST-cut quartz in room temperature, this SAW device can be a good candidate for field applications. From an early IDTs design, investigation in material and IDTs configuration is necessary to improve signal quality in order to qualify for liquid phase cell-based bio-sensing applications. A simplified 3D unit cell FEM model is created to study the thickness effects of wave-guide and electrodes. Boundary conditions and assumptions are discussed in the modeling. The simulated eigenfrequency of SH mode is close to the theoretical fundamental frequency of the 64μm wavelength IDTs. The mass damping effects from gold electrodes is more significant than aluminum electrodes.